Inflammation and Risk of Depression in HIV: Prospective Findings From the Multicenter AIDS Cohort Study. Issue 11 (23rd October 2019) - Lu, Haidong; Surkan, Pamela J; Irwin, Michael R; Treisman, Glenn J; Breen, Elizabeth C; Sacktor, Ned; Stall, Ron; Wolinsky, Steven M; Jacobson, Lisa P; Abraham, Alison G
Abstract: Studies suggest that inflammation might be involved in the pathogenesis of depression. Individuals with human immunodeficiency virus (HIV) have a higher risk of depression and elevated inflammatory profiles. Despite this, research on the link between inflammation and depression among this high-risk population is limited. We examined a sample of men who have sex with men from the Multicenter AIDS Cohort Study in prospective analyses of the association between inflammation and clinically relevant depression symptoms, defined as scores >20 on Center for Epidemiological Studies Depression Scale. We included 1, 727 participants who contributed 9, 287 person-visits from 1984 to 2010 (8, 218 with HIV (HIV+) and 1, 069 without (HIV−)). Exploratory factor analysis (EFA) was used to characterize underlying inflammatory processes from 19 immune markers. Logistic regression with generalized estimating equations was used to evaluate associations between inflammatory processes and depressive symptoms stratified by HIV serostatus. Three EFA-identified inflammatory processes (EIPs) were identified. EIP-1 scores—described by soluble tumor necrosis factor receptor 2 (sTNF-R2), soluble interleukin-2 receptor α (sIL-2Rα), sCD27, B-cell activating factor, interferon γ-induced protein 10 (IP-10), soluble interleukin-6 receptor (sIL-6R), sCD14, and sGP130—were significantly associated with 9% higher odds of depressive symptoms in HIV+ participants (odds ratio = 1.09; 95% confidence interval: 1.03, 1.16) and 33% higher odds in HIV− participants (odds ratio = 1.33; 95% confidence interval: 1.09, 1.61). Findings suggest that immune activation might be involved in depression risk among both HIV+ and HIV− men who have sex with men.